Microbiological testing of clinical samples before and after periodontal treatment. A comparative methodological study between real‐time PCR and real‐time‐PCR associated to propidium monoazide - Sereti, Maria; Zekeridou, Alkisti; Cancela, Jose; Mombelli, Andrea; Giannopoulou, Catherine (Clinical and experimental dental research, 2021)
Objectives The aim of the present methodological study was to evaluate the discrepancies in the detection of a number of periodontally involved pathogenic bacteria obtained from clinical samples by two methods: the quantitative Polymerase Chain Reaction (qPCR) and the qPCR combined with pre‐treatment by Propidium Monoazide (PMA). Material and methods Plaque and saliva samples were obtained from 30 subjects: 20 subjects with chronic or aggressive periodontitis in need of periodontal therapy with or without antibiotics and 10 subjects in Supportive Periodontal Treatment (SPT). The clinical samples taken before treatment (BL) and 1 month later (M1), were divided in two aliquots: one was immediately treated with PMA while the other was left untreated. All samples were further analyzed with qPCR after DNA extraction, for the detection of Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Tannerella forsythia (Tf), Treponema denticola (Td), Parvimonas micra (Pm), and Prevotella intermedia (Pi). Results Large inter‐individual variations were observed in the concentration of the studied bacteria. At both instances (BL and M1) and for the three groups, significantly lower counts of bacteria were depicted when plaque and saliva samples were pre‐treated with PMA as compared to those without treatment. Treatment resulted in significant decreases in the number of bacteria, mainly in the plaque samples. However, these changes were almost similar in the three groups independently of the method of detection used (PMA‐qPCR vs. q‐PCR). Conclusion Removal of DNA from non‐viable cells with PMA treatment is an easily applied step added to the classical qPCR that could give accurate information on the presence of viable bacterial load and evaluate the response to periodontal treatment.